Coping Strategies for Sexual Problems and Sexual Dysfunction Amongst Malay Women With Breast Cancer. A Qualitative Study - Siti Nuryati Che Ya, MMED Fam Med; Rosediani Muhamad, PhD; Norhasmah Mohd Zain, PhD; Rosnani Zakaria, FRACGP; Azlina Ishak, MMED Fam Med; Intan Idiana Hassan, PhD; Imisairi Ab Hadi, MMED Surg; Maya Mazuwin Yahya, MMED Surg; Wah Yun Low, PhD; Pranee Liamputtong, PhD (Sexual Medicine, 2021)
Introduction: Women’ sexuality becomes complex after breast cancer diagnosis and sexual health is highly neglected in the management of the illness. Aims: To explore the coping and strategies to overcome sexuality problems and sexual dysfunction among women with breast cancer. Material and Methods: Using the in-depth and photo-elicitation interview methods, this qualitative study following phenomenological analysis was conducted on fourteen married female respondents with breast cancer and had the positive result for female sexual dysfunction (FSD) screened by Female Sexual Function Index (FSFI-6 items) from Kelantan, Malaysia. The interviews data were audio-recorded, transcribed verbatim and managed in analytic computer software NVivo11 Pro. The transcriptions were analyzed using thematic analysis by referring to the meaning-making theory. Main Outcome Measures: We identified overlapping themes of coping and strategies among women with breast cancer to overcome sexual problems and sexual dysfunction which correspond with meaning-making theory. Results: Three themes have emerged. Women with breast cancer that developed sexuality problem and sexual dysfunction strived to accept the illness using religious belief and conform by altering sexual practices. These individuals positively look for a solution by seeking formal healthcare advice, modify their physical appearance, active discussion with the husband and support from other survivors. A few of them passively struggle with the subject by averting the intimacy and receptive toward polygamy. Conclusion: This study highlighted the various mechanisms that emphasized the pivotal role of religious belief and relationship context as key factors in the coping strategies among women with breast cancer in Malaysia. The finding may not be generalized to other countries.Che Ya SN, Muhamad R, Zain NM, et al. Coping Strategies for Sexual Problems and Sexual Dysfunction Amongst Malay Women With Breast Cancer. A Qualitative Study. Sex Med 2021;9:100336.